The regional map of Africa: Identity and ambivalences - Waldman, Maurício (Journal of Central and Eastern European African Studies, 2023)
Maps are the most relevant contribution of geography to the interpretation of human presence in space. The Cartography of Africa is a central issue in the global order. The continent projects importance in several different themes, including the dynamics of the continental economy and its insertion with the regionalization. The cartographic production centered on the African experience is largely unknown. Commonly it is omitted due to the almost atavistic disqualifying perspective surrounding the continent, its peoples, and cultures. Therefore, the Africa Map demands fair debate and recognition. In May 1961, when the continent was witnessing the emergence of a veritable flood of independences, the UN Economic and Social Council initiated the United Nations Regional Cartographic Conference for Africa. Intending to standardize geoinformation in the continent, the Regional Map of Africa is one of the most relevant developments of this initiative. Approved in February-March 1976 at the 26th Ordinary Session of the Council of Ministers of the Organization of African Unity, the Regional.